En Nuestra Casa No Hay Chinchorros: A Youth-Oriented, Participatory Approach to Chagas Prevention in Guara, Loja Province, Ecuador - Bates, Benjamin R.; Sharma, Devendra; Baus, Esteban G.; Grijalva, Mario J. (Frontiers in Communication, 2020)
Chagas disease is a neglected tropical disease that disproportionately affects impoverished rural communities. Insecticide-based approaches are inconsistently performed and exorbitantly priced for the communities affected. The present study considers an alternative approach to primary prevention of Chagas disease using entertainment education. As part of an ongoing effort in rural Ecuador, we worked with the children of the community of Guara, national insect control workers, and academicians to co-develop a song to promote behaviors related to preventing Chagas. Through an analysis of the song, we demonstrate opportunities for meaningful intervention in rural communities, as well as challenges to implementing an entertainment education approach when working with national stakeholders.